No title, no name, nothing, maybe waste - Meylahn, Johann-Albrecht (HTS teologiese studies, 2014)
There is general agreement that the globe is facing a crisis of the Anthropocene. The crisis has taken on such dimensions that a new way of thinking has become necessary. Or maybe a new way of being has become necessary, or maybe a new way of being thought has become necessary. What transformations (Verwandlungen) are necessary to arrive at this way of being thought? Maybe Nietzsche’s three transformations can guide towards a new way of being thought towards the Übermensch of the Anthropocene.